Public history: Private secret - Minnicelli, Mercedes S. (Clinical Styles. The Journal on the vicissitudes of childhood, 2000)
In the context of the studies on psychoanalysis and infancy, in this article are exposed inquiries and reflections that arise from the analysis of the author's practice and experience as a former chief of the Direction, a municipal public service of the city administration (Mar del Plata, Argentina). This case, the public history about a child who lives in the streets, renovates questions about the consequences of the constitution of the subject, when the minority discourse tries to sign the direction of the life.